eTechnology. Perl: the duct tape of the Internet. - Blansit BD (Journal of Electronic Resources in Medical Libraries, 2006)
Perl (Practical Extraction and Report Language) is a computer programming language with both the flexibility and ease to write code for quick tasks and the strength and stability to handle highly sophisticated, mission critical tasks. Available under the GNU-General Public License and supported by an active and wide user community, it has been expanded to an extremely wide range of applications. Often, programming involves making minor changes to preexisting programs.